The imaginary geography of Hollywood cinema 1960-2000 - Long, Christian B., 1975- (Intellect, 2017)
The Imaginary Geography of Hollywood Cinema 1960-2000 combines digital cartography with close readings of representative films from 1960 to 2000. Christian B. Long offers a unique history of twentieth century Hollywood narrative cinema, one that is focused on the intersection of the geographies of narrative location, production, consumption, and taste in the era before the rise of digital cinema. Long redraws the boundaries of film history, both literally and figuratively, by cataloging films' narrative locations on digital maps in order to illustrate where Hollywood actually locates its narratives over time.